2017
DOI: 10.1097/iae.0000000000001215
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-Seven-Gauge Versus 25-Gauge Vitrectomy for Primary Rhegmatogenous Retinal Detachment

Abstract: The safety and efficacy of 27-G PPV for rhegmatogenous retinal detachment appear similar to 25-GPPV. We found no anatomical or functional difference in terms of postoperative BCVA, IOP, complications, and operating time. Twenty-seven-G vitrectomy is therefore a valid option in the treatment of rhegmatogenous retinal detachment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
52
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(68 citation statements)
references
References 38 publications
14
52
1
1
Order By: Relevance
“…In both groups, the anatomical success rate was similar to the one described in earlier reports which reported an anatomic success rate with a single procedure ranging from 74% to 95% using 25-G PPV [10, 1216]. Therefore, although definitive comparisons between studies are usually difficult, as they differ in many parameters, our results showed that 27-G TSV was as effective as 25-G in reattaching the retina after initial surgery.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In both groups, the anatomical success rate was similar to the one described in earlier reports which reported an anatomic success rate with a single procedure ranging from 74% to 95% using 25-G PPV [10, 1216]. Therefore, although definitive comparisons between studies are usually difficult, as they differ in many parameters, our results showed that 27-G TSV was as effective as 25-G in reattaching the retina after initial surgery.…”
Section: Discussionsupporting
confidence: 88%
“…Over the past several years, recent innovations, such as the advent of powerful light sources, stronger instruments, and high-performance vitrectomy machines, have led to the development of a 27-gauge (27-G) transconjunctival sutureless vitrectomy (TSV) system [2]. The feasibility of this new microincision vitrectomy surgery (MIVS) has been recently demonstrated for various vitreoretinal diseases [210], including rhegmatogenous retinal detachment (RRD) [46, 810]. However, to our knowledge, to date, there is only one comparative study between 27-G and 25-G vitrectomy systems for RRD [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the feasibility of 27G MIVS has been demonstrated for various vitreoretinal diseases, including primary rhegmatogenous retinal detachment (RRD) [ 6 12 ]. However, there are only two prospective, comparative studies between 27G and 25G MIVS for RRD in a relatively small number (30 to 40 eyes) of patients so far [ 10 , 13 ]. The purpose of this study was to retrospectively compare the safety and effectiveness of 27G MIVS with 25G MIVS for the treatment of primary RRD in 92 patients.…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral shaving in this situation is more time-consuming and is more likely to require scleral depression by a skilled assistant due to reduced rigidity of the instruments. 17 Second, laser barricade of anterior breaks may similarly require scleral depression or a chandelier light source depending on the relationship of the break to the sclerotomy sites since there is no illuminated endolaser option.…”
Section: Practical Retinamentioning
confidence: 99%